Removal of Pb(II) ions from aqueous solutions by sulphuric acid-treated wheat bran - Ozer, A. (Elsevier, 2007)
Sulphuric acid-treated wheat bran (STWB) was used as an adsorbent to remove Pb(II) ions from aqueous solution. It was observed that the adsorption yield of Pb(H) ions was found to be pH dependent. The equilibrium time for the process was determined as 2 h. STWB gave the highest adsorption yield at around pH 6.0. At this pH, adsorption percentage for an initial Pb(II) ions concentration of 100 mg/L was found to be 82.8 at 25 degrees C for contact time of 2 h. The equilibrium data obtained at different temperatures fitted to the non-linear form of Langmuir, Freundlich and Redlich-Peterson and linear form of Langmuir and Freundlich models. Isotherm constants were calculated and compared for the models used. The maximum adsorption capacity (q a,) which was obtained linear form of Langmuir model increased from 55.56 to 79.37 mg/g with increasing temperature from 25 to 60 degrees C. Similar trend was observed for other isotherm constants related to the adsorption capacity. Linear form of Langmuir isotherm data was evaluated to determine the thermodynamic parameters for the process. Thermodynamic parameters show that adsorption process of Pb(II) ions is an endothermic and more effective process at high temperatures. The pseudo nth order kinetic model was successfully applied to the kinetic data and the order (n) of adsorption reaction was calculated at the range from 1.711 to 1.929. The values of k(ad) were found to be 5.82 x 10(-4) and 21.81 x 10(-4) (min(-1))(mg/g)(1-n) at 25 and 60 degrees C, respectively. Activation energy was determined as 29.65 kJ/mol for the process. This suggest that the adsorption Pb(II) ions by STWB is chemically controlled. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: wheat bran; sulphuric acid; adsorption; Pb(II) ions